People who could read Chilcas. The early diffusion of writing among the mapuche people (1775-1818) (Quinto Sol, 2019)
In this article we analyze the early process of incorporation of reading and writing in Mapuche society in the last third of the 18th century and the first decades of the 19th century. The possible mechanisms used to acquire this new technology are presented, while at the same time indigenous peoples ensured the services of effective and loyal cultural mediators, and their results.
Keywords: mapuche people; literacy; cultural mediators